STUDI LITERATUR : STANDAR PENERAPAN AKUNTANSI PAJAK PENGHASILAN PASAL 21 ATAS GAJI ASN - -, Nur Fadillah Padli; Faidul Adzim (Indonesian Journal of Research in Economy, 2023)
PPh Article 21 is the taxpayer's obligation to pay tax on income received, including salary, honorarium, allowances and other payments related to work, services or activities carried out by domestic individual taxpayers. The law that regulates tax rates, payment procedures and tax reporting is Law no. 36 of 2008. This research aims to analyze the calculation of PPh Article 21 on the salaries of State Civil Servants (ASN). The analytical method used is a descriptive method, which includes collecting, breaking down, calculating, comparing and explaining circumstances to reach conclusions. The results of the analysis show that the calculation of Income Tax Article 21 is in accordance with Taxation Law No. 36 of 2008, however, it is recommended that there be further calculation details to make it easier for employees to understand accounting calculations and records in accordance with Income Tax Article 21.